Nurse's perceptions of barriers to optimal nutritional therapy for hospitalized patients. (December 2017) - Papier, Irina; Lachter, Jesse; Hyams, Gila; Chermesh, Irit
Summary: Background & aims: Nurses have crucial roles in optimizing nutritional therapy for patients. The aim of this study was to explore nurses' perceptions regarding barriers to effective nutritional therapy. Methods: Hospital-based nurses completed a questionnaire regarding various aspects of malnutrition/risk identification and barriers to effective nutritional treatment. The study was conducted at Rambam Health Care Campus with 100 nurses completing the questionnaire. Results: Eighty-eight percent of those surveyed perceived identification of patients at risk for malnutrition as the nurse's responsibility. Significant differences were found when comparing head vs. bedside nurses regarding recognition of barriers to optimal nutritional therapy. More than 40% of the nurses found that the following issues were significant barriers to optimal patient treatment: the time it takes to prescribe nutritional therapy, lack of protocols, and awareness of the staff of the nutritional therapy. Overall bedside nurses found significantly more barriers preventing optimal nutritional therapy than did head nurses. Conclusions: Barriers to optimal nutrition are often remediable. Head nurses set ward policies but had a significantly different perception of barriers to nutritional care than bedside nurses. Collaboration is imperative for all sectors and authorities involved in patient care, including bedside nurses, to ensure that workable policies are implemented for the patients' benefit.